Assessment of Electric Power and Refrigeration Production by Using Solar Thermal Energy for lndustrial Applications - Guillermo Martínez-Rodríguez; Juan-Carlos Baltazar; Amanda L. Fuentes-Silva (Chemical Engineering Transactions, 2022)
Solar thermal energy can supply the total or partial thermal load in low-temperature industrial processes. In industry, applications of solar thermal energy may extend to produce electric power and refrigeration in a viable way. This work proposes a solar system composed by a storage system, low-temperature solar collector field, an organic Rankine cycle, and an absorption refrigeration system (Water/Lithium Bromide) to produce electric power and refrigeration. To evaluate the system performance, and its thermal and economic feasibility, an analysis, both in a continuous process and in a batch process, of a food industry was conducting. By this way, was possible to find operating conditions based on competitive cost of energy and decreasing CO2 emissions. An absorption refrigeration system with a thermal load value of 176 kW, and a thermal performance coefficient (COP) of 0.87, had a thermal solar energy levelized cost (LCOEth) of 0.0588 USD per kWh. ORC electric energy (LCOEele) had a charge of 0.1089 USD per kWh and a thermal efficiency of 0.11. Energy costs in kWh showed to be competitive, since they are in the order of the prices of conventional sources of energy, additionally, the emissions can reduce to zero.